Protective Effect of Empagliflozin (Sodium Glucose Co-transporter 2 Inhibitors) on pancreatic damage Induced by Streptozotocin in Adult Male Albino Rats - Medhat Atta Salah,; Mohamed Ahmed Desouky,; Youssra Magdy Hassan,; Abdel Hamid Sayed Abo Bakr, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Sodium glucose co-transporter 2 (SGLT2) inhibitors are primarily utilized for controlling blood sugar levels in individuals with type 2 diabetes. These drugs work by inhibiting the reabsorption of glucose in the kidneys, leading to its elimination through urine and thereby lowering blood glucose concentrations. Recent studies have expanded their potential benefits, suggesting that SGLT2 inhibitors may also offer protective effects in various tissues by reducing inflammation and mitigating oxidative stress, both of which play a critical role in the development of organ damage damage.Streptozotocin (STZ) is a naturally occurring antibiotic derived from Streptomyces achromogenes. In medicine, it is primarily used as a chemotherapy agent to treat certain types of pancreatic neuroendocrine tumors. STZ selectively targets insulin-producing beta cells, making it useful for managing insulin-secreting tumors. Its ability to cause beta-cell destruction has also made it a key compound in diabetes research for inducing experimental models of diabetes in animals. Aim:The aim of this study was to evaluate the potential protective effects of Sodium Glucose Co-transporter 2 (SGLT2) inhibitors on pancreatic damage caused by streptozotocin in male albino rats. This has been achieved through a combination of histological, immunohistochemical, and biochemical analyses to assess the extent of pancreatic damage and the potential therapeutic benefits of SGLT2 inhibition in mitigating inflammation, oxidative stress, and cellular injury. Materials and Methods:Forty adult male albino rats were used in this study, divided into four distinct groups. Group I (Control Group) consisted of 10 rats thatadministered three ml distilled water orally once daily. Group II included 10 rats that were administered Jardiance (Empagliflozin, an SGLT2 inhibitor) at a dose of 10 mg/kg/day, dissolved in drinking water for a period of 28 days. Group III included 10 rats that were fasted for 12 hours and then given a single high dose of streptozotocin (50 mg/kg) intraperitoneally to induce pancreatic damage. Group IV involved 10 rats that received Jardiance (Empagliflozin) at the same dose of 10 mg/kg/day for 14 days before being injected with streptozotocin (50 mg/kg) intraperitoneally andcontinued to receive the daily dose of Jardiance for 14 days during the post-STZ period. At the end of the study (28 days), pancreatic tissues were collected from all groups and processed for H&E staining and immunohistochemical analysis.Biochemical analyses were conducted to assess levels of glutathione (GSH), malondialdehyde (MDA), superoxide dismutase (SOD), as well as serum glucose and serum insulin levels. Results:The structural integrity of the pancreas in Group III was compromised, with destruction of the pancreatic architecture and islet cell disruption. The demarcation between the islets and the surrounding pancreatic acini was poorly defined. Additionally, degenerative changes and apoptosis were evident. However, the use of SGLT2 inhibitors provided significant protection, leading to a marked reduction in these effects and demonstrating a notable protective role in preventing pancreatic damage. Conclusion: .Sodium-Glucose Co-transporter 2 (SGLT2) inhibitors significantly reduce the degenerative damage caused by streptozotocin in the pancreas. The observed protective effects were reflected in the maintenance of pancreatic architecture, a decrease in inflammatory cell infiltration and a reduction in apoptosis. These findings suggest that SGLT2 inhibitors could serve as a promising therapeutic approach to protect pancreatic tissue from pancreatic damage.